2013
DOI: 10.3928/00220124-20130501-78
|View full text |Cite
|
Sign up to set email alerts
|

From Lecture to Learning Tasks: Use of the 4C/ID Model in a Communication Skills Course in a Continuing Professional Education Context

Abstract: This article describes the use of four-component instructional design (4C/ID), a model to plan educational interventions for complex learning. This model was used to design a continuing education course on communication skills for health professionals in a context that is hierarchical and communal. The authors describe the 4C/ID model and provide an example of its application in designing the course. In the 4C/ID model, learning tasks serve as the backbone of the course, with lectures and other supportive info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…Examples of task-centred models are cognitive apprenticeship (Brown, Collins, & Duguid, 1989), elaboration theory (Reigeluth, 1999), first principles of instruction (Merrill, 2002) and the four-component instructional design model (4C/ID model) ( van Merriënboer, 1997). The 4C/ID model is characterised by a strong research base and a spreading popularity, as evidenced by the increasing number of publications in various contexts, such as medical education (Maggio, Cate, Irby, & O'Brien, 2015), communications training (Susilo, van Merriënboer, van Dalen, Claramita, & Scherpbier, 2013), technical training (Sarfo & Elen, 2007), information problem-solving (Wopereis, Frerejean, & Brand-Gruwel, 2015), and teacher training (Kreutz, Leuders, & Hellmann, 2019). The accompanying Ten Steps approach (van Merriënboer & Kirschner, 2018) provides guidelines for analysing real-life tasks in order to uncover the different types of knowledge and skills needed in daily practice (cognitive task analysis) and guidelines for designing a blueprint for an educational programme comprising four components: learning tasks, supportive information, procedural information and part-task practice.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of task-centred models are cognitive apprenticeship (Brown, Collins, & Duguid, 1989), elaboration theory (Reigeluth, 1999), first principles of instruction (Merrill, 2002) and the four-component instructional design model (4C/ID model) ( van Merriënboer, 1997). The 4C/ID model is characterised by a strong research base and a spreading popularity, as evidenced by the increasing number of publications in various contexts, such as medical education (Maggio, Cate, Irby, & O'Brien, 2015), communications training (Susilo, van Merriënboer, van Dalen, Claramita, & Scherpbier, 2013), technical training (Sarfo & Elen, 2007), information problem-solving (Wopereis, Frerejean, & Brand-Gruwel, 2015), and teacher training (Kreutz, Leuders, & Hellmann, 2019). The accompanying Ten Steps approach (van Merriënboer & Kirschner, 2018) provides guidelines for analysing real-life tasks in order to uncover the different types of knowledge and skills needed in daily practice (cognitive task analysis) and guidelines for designing a blueprint for an educational programme comprising four components: learning tasks, supportive information, procedural information and part-task practice.…”
Section: Introductionmentioning
confidence: 99%
“…As noted, whole-task approaches provide opportunities for learning transfer11 12 and have been implemented in medical education 13 14. Building on such findings, this project demonstrates additional benefits to a whole-task approach for EBM teaching, such as increased engagement with uncertainty and student opportunities for legitimate peripheral participation.…”
Section: Discussionmentioning
confidence: 66%
“…Although whole-task approaches for teaching communication13 and clinical reasoning14 in medical education have been reported, there are few accounts of whole-task activities for teaching and practising EBM. One recent paper describes efforts to integrate whole-task activities in a clerkship curriculum in the form of educational prescriptions 15.…”
mentioning
confidence: 99%
“…Recently, the use of wholetask learning to teach complex tasks has become popular 27 and has been applied in teaching medical topics. 28 Researchers have identified that whole-task learning approaches provide learners with a holistic model of how to practice EBM and have linked these approaches to learners' increased ability to transfer skills into practice. 21,29 Whole-task learning approaches are the foundation for several instructional design approaches, 30 This study describes challenges to students learning EBM and the educational approaches used by a select sample of medical schools to overcome these challenges.…”
Section: Discussionmentioning
confidence: 99%